STUDI KELAYAKAN FINANSIAL USAHA PETERNAKAN AYAM RAS DENGAN POLA KEMITRAAN DI KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Siringo-ringo, Arman (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2016)
Ranch agribisnis is all business activities related to livestock farming activities, the farm is able to improve the rural economy and increase rural incomes ( Sutawi, 2012). The aims of the study : (1) identify the system of chicken management ranch business by plasma partnership system with PT.Gemilang Unggas Prima.(2) analyze feasibility financial of chicken ranch business by plasma partnership system with PT. Gemilang Unggas Prima.(3) analyze the sensitivity of the chicken farm in the district race Rambah Hilir to the possibility of an increase in operating expenses and adecrease in selling prices together. This research was conducted from october 2015 until february 2016. Data collection methods used are surveys and direct interviews with respondents. Broiler breeding business through a partnership with the companyâs core ( PT.gemilang Unggas Prima) started based on a cooperation agreement that governs all the scope of the partnership includes the benefit and risks of each party effort that must be borne. To meet the obligation of duty as the core enterprise of the plasma business, in this partnership , PT.Gemilang unggas Prima provide a means of livestock production (DOC, fodder, and medicines), equipment enclosures, technology guidance, marketing and payment of the rest of the plasma business. Based on the results of a financial analysis broiler breeding business with a partnership with the scale maintenance 20.000, 13.000, 12.000, 8.000 and 7.000, deserves to be developed , because all the qualified investment feasibility analysis of the five farmers with loan capital from Bank with interest rate of 16%. Where in the resulting NPV is greater than 0, net B/C is greater than 1, the IRR is greater than the discount factor. And the length of time needed to cover investment back relatively quickly (PP) sensitivity analysis on theÂ  increase in operating costs together amounted to 10% and 10% decrease in selling prices. Broiler farms business is still feasible to be developed.